Next-Generation Transportation: Smart Electric Tricycle Integrated with IoT Technology - Ramisetty Umamaheswari; Karanam Jahnavi; Gandepalli Tejaash; Gannamraju Alekhya; Vangamudi Nikhil; Neerukonda Lokeswara Rao (Engineering Proceedings)
The aim of the electric tricycle is to bring increased mobility to impaired persons. Presently, hand-powered tricycles are used by numerous members of the impaired community, but some current users of hand-powered tricycles do not have the physical strength or collaboration to propel themselves on the tricycle with their arms and hands. The aim of the proposed paper is to add electric power to the current hand-powered tricycle to provide tricycle users with improved mobility, providing them with more freedom and making a donation to the community. This paper develops an inclusive and cost-effective electric tricycle designed specifically for individuals with mobility challenges. The proposed tricycle is equipped with a 350-watt motor and has a cargo capacity of over 100 kg. Using IoT technology, the proposed system includes features similar to real-time position shadowing, on/off announcements through mobile and dispatch, and clear on/off suggestions. This innovative result addresses the unique requirements of hindered individuals, promoting availability, autonomy, and enhanced mobility in a socially conscious manner.